Bintang Supermarket's Strategy in Maintaining Customer Loyalty through the Ukhuwah Insaniyah Approach - Aris Ashar; Amin Wahyudi (al-Afkar, Journal For Islamic Studies, 2025)
Customer loyalty is key to long-term success for any company, including Bintang Swalayan. This study examines the strategies implemented by Bintang Swalayan to maintain customer loyalty by integrating the principles of Ukhuwah Islamiyah, which include honesty, fairness, and caring. This approach focuses on transparent service, quality halal products, and fair prices. Furthermore, the supermarket offers loyalty programs that accommodate Islamic values, such as special discounts on Islamic holidays. In this way, Bintang Swalayan successfully builds strong and emotional relationships with customers, creating a shopping experience that is not only satisfying but also meaningful. The methodology used is qualitative with a focus on a literature review to explore the applied principles of Islamic economics. The results show that service quality, customer satisfaction, and an effective loyalty program play a significant role in building loyalty. By implementing the principles of Ukhuwah Islamiyah, Bintang Swalayan not only increases customer satisfaction but also strengthens social bonds within the Muslim community. Through this strategy, Bintang Swalayan strives to create a fair and prosperous business environment, while strengthening its position in a competitive market.